IDDF2019-ABS-0137 Is microscopic colitis(MC) restricted to colon? study of ileal changes in patients of MC. (June 2019) - Singh, Anupam Kumar; Shukla, Siddharth; Kochhar, Rakesh; Bellam, Balaji L; Rana, Satyavathi; Prasad, Kaushal K; Dhaka, Narender; Malik, Sarthak; Berry, Neha; Sharma, Megha; Sinha, Saroj Kant
Abstract : Background: Chronic diarrhea due to Microscopic colitis (MC) is often overlooked . Restriction of disease to the colon is still unclear, and on drawing analogies from Idiopathic Ulcerative Colitis any proximal disease extension may have bearing on treatment regimes. We evaluated terminal ileum using narrow band imaging (NBI), high definition white light endoscopy (HDWLE) and histopathological findings on biopsy Methods: 53 adults with suspected MC were enrolled. All underwent colonoscopy with ileal intubation. Segmental colonic and terminal ileum biopsies were obtained using HDWLE and NBI. Same were analysed by expert gastrointestinal histopathologist Results: In 43 patients of confirmed MC, HDWLE of ileum was normal. On NBI, intravillous capillary network was regular unbranched with semi-circular pattern in 41(95.4%) of patients of MC and in all controls. It was sparse and irregular in 2(4.7%) cases. Peyer's patch domes were indistinct in 5(9.4%), normal in 38(88.4%) cases and normal in all controls (p = 0.570). Peyer's patch vessels were regular and unbranched in 38(88.4%) cases and all controls. They were sparse and irregular in 5 cases (11.6%) (p = 0.570). Ileal histopathology revealed normal villi in 39 (90.6%) cases, 4 had partial villous atrophy. The crypt villous ratio was grouped as 1:1.5, 1:3, 1:4 and 1:5 in 2 (4.6), 26 (60.4), 11 (25.5%) and 4 (9.3) respectively. Lymphoplasmacytic infiltrate was grouped as mild, moderate and severe, and observed in 10 (23.2%), 2 (4.6%) and 1 (2.3%) patient respectively Conclusions: Ileal NBI findings in MC are hitherto unreported, with up to 12% showing abnormalities. Histologically up to 23% showed abnormalities in ileal biopsies. Ileal pathology may contribute to certain symptoms in MC